The effect of the 50:22 law trial on the Currie Cup and Varsity Cup rugby tournaments between 2021 and 2022 - Strydom, Wikus (Stellenbosch : Stellenbosch University, 2023)
Thesis (M Sport Sc)--Stellenbosch University, 2023.